Induced expression modes of genes related to Toll, Imd, and JAK/STAT signaling pathway-mediated immune response in Spodoptera frugiperda infected with Beauveria bassiana - Li, Jihu; Mao, Yongkai; Yi, Jiequn; Lin, Mingjiang; Xu, Hanliang; Cheng, Yinjie; Wu, Han; Liu, Jianbai (Frontiers in Physiology, 2023)
Spodoptera frugiperda is one of the most harmful pests of maize and other major food and causes huge economic loss every year in China and other countries and regions.Beauveria bassiana, as a kind of entomological fungi that is highly pathogenic to pests, is harmless to the environment and human beings; while, at present, S. frugiperda has gradually developed resistance to many pesticides and microbial insecticides. In this study, transcriptome sequencing was conducted to analyze the differences in gene expression between infected and uninfected S. frugiperda with B. bassiana. More than 160 Gb of clean data were obtained by using the Illumina HiSeqTM 4,000 platform as 150 bp paired-end reads, and 2767 and 2892 DEGs were identified in LH36vsCK36 and LH144vsCK144, respectively. In order to explore the roles of Jak/STAT, Toll and Imd signaling pathways in antifungal immune response in S. frugiperda against B. bassiana infection, the expression patterns of those signaling pathways-related genes in S. frugiperda challenged by B. bassiana were analyzed using quantitative real-time PCR. In addition, antifungal activity experiments revealed that the suppression of JaK/STAT, Toll and Imd signaling pathways by inhibitors could inhibit the antifungal activity to a large extent and lead to an increased sensitivity of S. frugiperda to the challenge of B. bassiana, indicating that JaK/STAT, Toll and Imd signaling pathways and the genes associated with these signaling pathways might be involved in the synthesis and secretion of antifungal substances. This study implied that JaK/STAT, Toll and Imd signaling pathways played crucial roles in the antifungal immune response of the S. frugiperda larvae, in which the related genes of those signaling pathways could act as special regulatory roles in signal transduction. This study would improve our understanding of the molecular mechanisms related to innate immunity and provide the basis for a wide spectrum of strategies to against resistance of the antifungal of S. frugiperda.